Stan & Ollie [videorecording (DVD)] - Coogan, Steve; Reilly, John C., 1965-; Arianda, Nina; Henderson, Shirley, 1965- (Sony Pictures Home Entertainment, 2019)
One of the world's great comedy teams set out on a variety hall tour of Britain in 1953. Diminished by age and with their golden era as the kings of Hollywood comedy now behind them, they face an uncertain future. As the charm and beauty of their performances shine through, they re-connect with their adoring fans. The tour becomes a hit, but Stan and Ollie can't quite shake the specter of Laurel and Hardy's past.